Application of Long-Chained Auxin Conjugates Influenced Auxin Metabolism and Transcriptome Response in Brassica rapa L. ssp. pekinensis - Smolko, Ana; Repar, Jelena; Matković, Marija; Pavlović, Iva; Pěnčík, Aleš; Novák, Ondřej; Ludwig-Müller, Jutta; Salopek-Sondi, Branka (International journal of molecular sciences, 2023)
Auxin amino acid conjugates are considered to be storage forms of auxins. Previous research has shown that indole-3-acetyl-L-alanine (IAA-Ala), indole-3-propionyl-L-alanine (IPA-Ala) and indole-3-butyryl-L-alanine (IBA-Ala) affect the root growth of Brassica rapa seedlings. To elucidate the potential mechanism of action of the conjugates, we treated B. rapa seedlings with 0.01 mM IAA-, IPA- and IBA-Ala and investigated their effects on the auxin metabolome and transcriptome. IBA-Ala and IPA-Ala caused a significant inhibition of root growth and a decrease in free IAA compared to the control and IAA-Ala treatments. The identification of free auxins IBA and IPA after feeding experiments with IBA-Ala and IPA-Ala, respectively, confirms their hydrolysis in vivo and indicates active auxins responsible for a stronger inhibition of root growth. IBA-Ala caused the induction of most DEGs (807) compared to IPA-Ala (417) and IAA-Ala (371). All treatments caused similar trends in transcription profile changes when compared to control treatments. The majority of auxin-related DEGs were found after IBA-Ala treatment, followed by IPA-Ala and IAA-Ala, which is consistent with the apparent root morphology. In addition to most YUC genes, which showed a tendency to be downregulated, transcripts of auxin-related DEGs that were identified (UGT74E2, GH3.2, SAUR, IAA2, etc.) were more highly expressed after all treatments. Our results are consistent with the hypothesis that the hydrolysis of conjugates and the release of free auxins are responsible for the effects of conjugate treatments. In conclusion, free auxins released by the hydrolysis of all auxin conjugates applied affect gene regulation, auxin homeostasis and ultimately root growth inhibition.
Keywords: Animals; Indoles; indoly; amino acid auxin conjugates; Indoleacetic Acids; indole-3-propionic acid; Gastropoda; indole-3-butyric acid; kyseliny indoloctové; transcriptome; plži; transkriptom; root growth inhibition; Brassica rapa; indole-3-acetic acid; zvířata; alanin; semenáček; Transcriptome; Seedlings; Alanine; auxin metabolome